Senior Policy 2.0? Proposition of Including Elements of Interaction and Technologization into Mainstream Senior Policies - Zapędowska-Kling, Kaja (Studia Oeconomica Posnaniensia, 2018)
This paper aims at creating theoretical foundations of a new concept of an "ageing policy 2.0" for Poland. With reference to the main priorities of the Web 2.0 philosophy, such as the popularising and development of new information and communication technologies (ICTs), mutuality and reciprocity in information exchange, and maximisation of interaction, this paper focuses on discussing a "participatory approach" in social policy and postulates further dissemination of gerontechnologies in the everyday practices of elderly people and their caretakers. The Author illustrates and discusses three main pillars of ageing policy 2.0, which are then exemplified by several good practices representing both a Polish and a foreign context. The paper attempts to answer the question whether it is possible to create modern welfare states with respect to the maxim nihil de nobis sine nobis, which means "nothing about us without us". The general concept of "ageing policy 2.0" is strictly linked to the idea of empowerment and thus it aims at strengthening seniors’ social and political position within a society.